Barriers to Play and Recreation for Children and Young People with Disabilities. Exploring Environmental Factors - Fenney Salkeld, Deborah (De Gruyter, 2017)
This report reviews international research into the barriers to play for children with disabilities. The authors come from different disciplinary backgrounds, in Sociology, Social Policy, Anthropology, Occupational Health and Education and bring different concerns to this review. They are united, however, in their adoption of a rights-based perspective. The UNCRC and UNCRPD emphasise the right to play for children with disabilities. Play is vital for child development. The problem of 'play deprivation' for many children with disabilities is very real. Yet the right to, and value of 'play for the sake of play', for fun and recreation, must not be forgotten in relation to the lives of children with disabilities. The focus in this report is upon barriers to play that exist beyond the minds and bodies of individual children, within a 'disabling' environment. Barriers include those associated with the design of the built environment, social attitudes and professional practices. The report maps an agenda for further research in this area, emphasising the need for participatory methodologies that capture the views and voices of children with disabilities, their friends and families, on this important issue of play.